Phyllopertha horticola Linné - Pest in blueberry plantations in the Mărişel area (Cluj County) - Ionuţ Bogdan HULUJAN; Teodora FLORIAN; Horia BUNESCU (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Agriculture, 2021)
Phyllopertha horticola Linné (Coleoptera: Scarabaeidae) is one of the most common phytophagous beetles in Central Europe. In 2020 the blueberry growers from the Mărişel area reported the presence of a new beetle that attacked the fruit’s flowers and leaves. The species was identified at the University of Agricultural Sciences and Veterinary Medicine in Cluj-Napoca as the garden chafer. In the following year, the plants attacked by the garden beetle were monitored in the blueberry plantation in the Mărişel area. For monitoring the garden chafer, three rows of land were randomly selected in each plot with intervals of 20 plants per row. Each plant was analyzed individually and the number of adult beetles reported on the plant was noted. The observations were made between June and July 2021. In the Elliot variety, the share of plants reported with adults of Phyllopertha horticola Linné was between 50% and 60%, the average being 55%. Regarding the maximum number of adults/plant, it was between 6 specimens (raw 1) and 9 adults/plant (raw 2). In the Bluecrop variety, the share of plants with adults of the monitored species was between 10% and 45%, with an average per variety of 25%.